The relationship between motor competence and executive function as influenced by age, sex, and family socio-economic status - Ghorbanzadeh, Behrouz; Orangi, Behzad Mohammadi; Sahin, Tolga (Frontiers in Psychology, 2025)
IntroductionMotor Competence (MC) plays a fundamental role in physical, cognitive, and social development, while executive function (EF) is a key factor influencing MC. The primary objective of this study was to compare MC across three age groups (children, adolescents, and young adults), sex, and socio-economic status (SES). The main aim was to investigate the relationship between MC and EF and to determine whether age, sex, and SES could modify this relationship.MethodsThis descriptive-correlational study evaluated 475 participants from three age groups (8–11, 12–15, and 18–21 years). MC was measured using the BOT-2 test, and EF was assessed with the Stroop test. Data were analyzed using independent t-tests, one-way ANOVA, and linear regression analysis.ResultsFindings revealed that MC was higher in children compared to adolescents and young adults, and higher SES was associated with better MC, whereas sex had no significant effect on MC. Additionally, a strong positive relationship (44%) was identified between EF and MC, with this relationship being moderated by age, sex, and SES.DiscussionThe results indicated that MC and EF are influenced by the interaction of individual (age and sex) and environmental (SES) constraints. These findings underscore the importance of incorporating these factors into educational and sports planning for more holistic development.